The Arabian influence in the Taureg music - Foedermayr, Franz (International Library of African Music, 1966)
The somewhat scanty literature on Tuareg music sometimes adopts contrary attitudes in regard to the problem of foreign influences. Holiday1 makes a rough division of the Ahaggar Tuareg songs into those showing negro influence and those with Moorish characteristics, without offering a closer definition of the term Moorish. However, it probably stands for the Maghreb blend of Berber-Arabian culture. Zoehrer, on the other hand, states that the Tuareg songs and airs must be clearly distinguished from those of the Arabs in North Africa and those of the Haussa in the South, that the Tuareg are still singing today (1935) almost exclusively their own original songs and that with very few exceptions they have made no musical borrowings of any kind from their Islamic neighbours to the north and south. Nikiprowetzky lists some characteristics of the Tuareg music of the Air, which are of Middle Eastern origin, but he, too, emphasizes the strict independence of the Tuareg music and its Berber origins. Lhote on the other hand notes the similarity between the Tuareg music and that of certain Berber tribes in the Atlas mountains and evidently relying on Hornbostel-Lachmann he considers certain analogies between this Berber music and South-Arabian music.
Keywords: Music; Tuaregs; Ethnomusicology; African Music; Arab Influences